Tailored medium-entropy Si alloy anodes with multi-element Fe-site substitution for high-performance Li-ion batteries - Byeong Guk Kim; Jung-Hyeok Park; Jihyeon Ryu; Kyungmin Do; Dong Gyun Hong; Tae-Hyun Kwon; Oh Sung Kwon; Insung Jang; Jaeik Hyun; Geon-Hyoung An; Youngoh Kim; Geon-Woong Lee; et al. (Chemical Engineering Journal, 2026)

Sediment facies regulate organic and shell-derived carbonate carbon storage in the Shinan tidal flats, Korea - Yoon-Seo Kim; Yeo-Bin Park; Ji-Won Park; Eui-Joo Kim; Sang-Pil Lee; Seung-Jun Lee; Do-Hun Ryu; Ji-Su Ko; Jun-Mo Kim; Jae-Hoon Park; Yong-Sik Hong; Sang-Kyoung Lee; et al. (Regional Studies in Marine Science, 2026)

A Flow Analysis Modeling Study on the Performance Characteristics of LNG-Fueled Gas Valve Unit - Jung-Wook Lee; Kyeong-Ju Kong; Do-Yeong Jeong; Seung-Hun Han (Journal of Marine Science and Engineering, 2026)
As climate change and air pollution problems become more serious around the world, regulations to reduce greenhouse gas emissions are being tightened. The International Maritime Organization (IMO) has adopted measures to limit sulfur oxides and nitrogen oxides generated by ships. Due to the continuous use of fossil fuels, carbon dioxide emissions are increasing rapidly, which is acting as a major cause of global warming and climate change. Currently, the carbon neutrality policy to reduce greenhouse gases emitted by ships is expanding, and the use of alternative energy from marine fuels is increasing worldwide. The shipbuilding industry is actively introducing eco-friendly ships that use liquefied natural gas (LNG) fuels, and the importance of equipment such as the Fuel Gas Supply System (FGSS), which can supply eco-friendly energy, is growing. In this study, we designed a Gas Valve Unit (GVU), one of the FGSS components, and analyzed the internal flow of the GVU by performing computational fluid dynamics (CFD) simulations.

Plant life form, biomass allocation, and belowground structure shape depth-dependent soil organic carbon accumulation as blue carbon sources in vegetated tidal flats - Jae-Hoon Park; Yeo-Bin Park; Ji-Won Park; Sang-Pil Lee; Do-Hun Ryu; Seung-Jun Lee; Jun-Mo Kim; Ji-Su Ko; Eui-Joo Kim; Yoon-Seo Kim; Young-Han You (Science of The Total Environment, 2026)

Atypical humidity-enhanced NO2 sensing in WO3 via Zn doping and visible-light activation: Mechanistic elucidation and application to breath analysis - Nguyen Thao Trinh Do; Byeong-Hun Yu; Sang-Won Lee; Yeon-Tae Yu; Ji-Wook Yoon (Chemical Engineering Journal, 2026)

Seasonal and geographical variations in the community structure of environmentally-transmitted symbiotic bacteria in Riptortus pedestris (Hemiptera: Alydidae) - Joo-Young Kim; Do-Hun Gook; Minhyung Jung; Doo-Hyung Lee (Journal of Asia-Pacific Entomology, 2024)

Acid-site control of ZSM-5 zeolites using quaternary ammonium hydroxides for shale gas dehydroaromatization - Yangho Jeong; Yong Hyun Lim; Eun Ji Choi; Hae Won Ryu; Jangeon Roh; Susung Lee; Minkee Choi; Do Heui Kim; Jong Hun Kang (Chemical Engineering Journal, 2024)

The therapeutic efficacy of silver loaded rhenium disulfide nanoparticles as a photothermal agent for cancer eradication - Sesha Subramanian Murugan; Won Hur; Seong Eun Son; Han Been Lee; Chang Hyeon Ha; Su Jeong Lee; Se Hwa Cheon; Do Hyeon Kim; Sung Min Jeon; Da Young Choi; Jayachandran Venkatesan; Gi Hun Seong (Journal of Photochemistry and Photobiology B: Biology, 2024)

Multi-organ metastases of primary chondrosarcoma of the mammary gland of a spayed Toy Poodle - Seung-Won Yi; A-Ra Cho; Yoon Jung Do; Young-Hun Jung; Han Gyu Lee; Eun-Yeong Bok; Tai-Young Hur; Sung-Lim Lee; Eunju Kim (Journal of Comparative Pathology, 2023)

Li reaction pathways in Ge and high-performance Ge nanocomposite anodes for Li-ion batteries - Dong-Hun Lee; Do-Hyeon Kim; Heechul Jung; Cheol-Min Park (Chemical Engineering Journal, 2023)

Complete mitochondrial genome of the invasive semi-aquatic mammal, nutria Myocastor coypus (Rodentia; Myocastoridae) - Do-Hun Lee; Moo-Seung Lee; Young-Chae Kim; Il Ryong Kim; Hye Kwon Kim; Dae Gwin Jeong; Jung Ro Lee; Ji Hyung Kim (Conservation Genetics Resources, 2018)

Interannual Variation of Surface Circulation in the Japan/East Sea due to External Forcings and Intrinsic Variability - Byoung-Ju Choi; Seong Hun Cho; Hee Seok Jung; Sang-Ho Lee; Do-Seong Byun; Kyungman Kwon (Ocean Science Journal, 2018)

Effects of microwaves on the reduction of Aspergillus flavus and Aspergillus parasiticus on brown rice ( Oryza sativa L.) and barley ( Hordeum vulgare L.) - Seung-Hun Lee; Shin Young Park; Kye-Hwan Byun; Hyang Sook Chun; Sang-Do Ha (Food Additives & Contaminants: Part A, 2017)

CCR5 deficiency increased susceptibility to lipopolysaccharide-induced acute renal injury - Dong Hun Lee; Mi Hee Park; Chul Ju Hwang; Jae Yeon Hwang; Hae Suk Yoon; Do Young Yoon; Jin Tae Hong (Archives of Toxicology, 2016)

Reducing Effect of IL-32α in the Development of Stroke Through Blocking of NF-κB, but Enhancement of STAT3 Pathways - Chul Ju Hwang; Hyung-Mun Yun; Yu Yeon Jung; Dong Hun Lee; Na Young Yoon; Hyun Ok Seo; Jin-Yi Han; Ki-Wan Oh; Dong Young Choi; Sang-Bae Han; Do Young Yoon; Jin Tae Hong (Molecular Neurobiology, 2015)

Blood levels of cadmium and lead in residents near abandoned metal mine areas in Korea - Dong-UK Park; Dae-Seon Kim; Seung-Do Yu; Kyeong-Min Lee; Seung-Hun Ryu; Soo-Geun Kim; Won-Ho Yang; Doo-Yong. Park; Yeong-Seoub Hong; Jung-Duck Park; Byung-Kook Lee; Jai-Dong Moon; et al. (Environmental Monitoring and Assessment, 2014)

Animal models of axon regeneration after spinal cord injury - Do-Hun Lee; Jae K. Lee (Neuroscience Bulletin, 2013)

Carpesium abrotanoides extract inhibits cyclooxygenase-2 expression induced by toll-like receptor agonists - Do-Won Jeong; Eun-Kyeong Lee; Chung-Ho Lee; Se Jin Lim; Gyo-Jeong Gu; Ji Hun Paek; Songmun Kim; Soon Sung Lim; Hyung-Sun Youn (Toxicology and Environmental Health Sciences, 2013)

mRNA sequence analysis and quantitative expression of the ADAMTS4 gene in the thoroughbred horse - Jae-Woo Moon; Kung Ahn; Jin-Han Bae; Gyu-Hwi Nam; Byung-Wook Cho; Kyung-Do Park; Hak-Kyo Lee; Young-Mok Yang; Tae-Hun Kim; Hwan-Hoo Seong; Kyudong Han; Heui-Soo Kim (Genes & Genomics, 2012)

Abnormal effects of unpurified and purified multi-walled carbon nanotubes in A549, Jurkat and THP-1 cell lines - Young Hun Kim; Hyeoung Woo Park; Zae Young Ryoo; Hyun-Shik Lee; Do-Hyung Kim; Sanggyu Lee (Molecular & Cellular Toxicology, 2012)

Novel PPARγ partial agonists with weak activity and no cytotoxicity; identified by a simple PPARγ ligand screening system - Min-Chul Cho; Dong-Hun Lee; Eun Jin Kim; Jee-young Lee; Jeong-Woo Kang; Jong Hwan Song; Youhoon Chong; Yangmi Kim; Jin-Tae Hong; Do-Young Yoon (Molecular and Cellular Biochemistry, 2011)

Oxidized phosphatidylcholine induces migration of bone marrow-derived mesenchymal stem cells through Krüppel-like factor 4-dependent mechanism - Sang Hun Shin; Hae Young Song; Min Young Kim; Eun Kyung Do; Jung Sub Lee; Jae Ho Kim (Molecular and Cellular Biochemistry, 2011)

Comparing the inverse parameter estimation approach with pedo-transfer function method for estimating soil hydraulic conductivity - Do-Hun Lee (Geosciences Journal, 2005)